Embodied interreligious engagement: Female gendered bodies, reconciliation, and sport in Djibouti - Jones, Rachel (Missiology, 2024)
Foreign Christian women in Muslim-majority countries may experience gendered culture shock and various forms of insidious trauma. This is rarely addressed by organizations or individuals yet has a significant impact on women, their communities, and their work by causing a rupture in their concept of self, community, and God. This article argues that participation in sports as intentional embodied interreligious engagement offers potential for Christian and Muslim women to mutually discover valuable resources for reconciling what trauma ruptures, namely their relationship with their own bodies and their communities. The article first establishes the experience of gendered culture shock, sexual harassment, and insidious trauma, and reasons Christians may downplay their impact. It then develops the concept of an incarnational ministry of reconciliation. This is followed by looking at how intentional interreligious engagement must begin on neutral ground and identifies sports as one possibility for embodiment in interreligious engagement. The article concludes with suggestions for further research and ideas for further embodied interaction, moving toward deeper and more intentional interreligious engagement.